Tantangan Pelestarian Budaya Lokal di Tengah Modernisasi: Studi Kasus pada Suku Muyu di Papua Selatan - Zahra, Nur Amalia; Koimah, Siti Mariyatul; Salam, Fitrah Febri (CV. Kurnia Grup, 2025)
This study examines the challenges of cultural preservation faced by the Muyu Tribe in South Papua amidst modernization, focusing on socio- cultural dynamics and indigenous adaptation strategies. The research addresses key issues including cultural value erosion, transformation of traditional knowledge systems, and tensions between customary institutions and modern governance structures. Employing a qualitative approach with systematic literature review methodology, Findings reveal that the Muyu Tribe maintains cultural resilience through three primary mechanisms: (1) reinterpretation of traditional values in modern contexts, (2) adaptation of customary institutions, and (3) innovation in intergenerational cultural transmission. Major challenges stem from culturally insensitive infrastructure development and limited community participation in development planning. The study emphasizes the need for rights-based cultural preservation approaches that integrate local wisdom with sustainable development, along with strengthening customary institutions' capacity in development governance. These findings contribute theoretically to development anthropology studies and offer practical implications for cultural policy formulation in indigenous territories.